Artemisinin-Ginkgo biloba extract combination therapy for Plasmodium yoelii. (February 2021) - Zhang, Qiang; Ao, Zhuo; Hu, Nan; Hu, Xiajun; Liao, Fulong; Han, Dong
Abstract: Malaria remains a widespread life-threatening infectious disease, leading to an estimated 219 million cases and around 435, 000 deaths. After an unprecedented success, the antimalarial progress is at a standstill. Therefore, new methods are urgently needed to decrease drug resistant and enhance antimalarial efficacy. According to the alteration of erythrocyte biomechanical properties and the immune evasion mechanism of parasites, drugs, which can improve blood circulation, can be chosen to combine with antimalarial drugs for malaria treatment. Ginkgo biloba extract (GBE), one of drug for vascular disease, was used to combine with artemisinin for Plasmodium yoelii therapy. Artemisinin-GBE combination therapy (AGCT) demonstrated remarkable antimalarial efficacy by decreasing infection rate, improving blood microcirculation and modulating immune system. Besides, the expression of invasion related genes, such as AMA1, MSP1 and Py01365, can be suppressed by AGCT, hindering invasion process of merozoites. This new antimalarial strategy, combining antimalarial drugs with drugs that improve blood circulation, may enhance the antimalarial efficacy and ameliorate restoration ability, proving a potential method for finding ideal compatible drugs to improve malaria therapy